2017
DOI: 10.3389/fnmol.2017.00099
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of Foldase and Chaperone Proteins Are Associated with an Early-Onset Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by a progressive upper and lower motor neuron degeneration. One of the peculiar clinical characteristics of ALS is the wide distribution in age of onset, which is probably caused by different combinations of intrinsic and exogenous factors. We investigated whether these modifying factors are converging into common pathogenic pathways leading either to an early or a late disease onset. This would imply the identification of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 62 publications
6
37
0
Order By: Relevance
“…Similarly, in the cortex of PPIA-/-mice, the 25-kDa TDP-43 fragment was significantly enriched in the detergent-insoluble fraction, while the full-length was not. Biochemical analysis of the detergent-insoluble fraction of the cortex of PPIA-/-mice indicated general increases in insoluble, ubiquitinated proteins and TIA1 stress granule marker, confirming PPIA's involvement in regulating protein homeostasis, as already suggested by other work in this laboratory (Filareti et al, 2017;Luotti et al, 2020). We recently reported that ALS patients have low PPIA levels and a concomitant shift toward increased protein partitioning in the insoluble fraction, with high levels of insoluble TDP-43 and hnRNPA2/B1 (Luotti et al, 2020).…”
Section: Ftld-tdp Is the Most Common Neuropathologic Type Of Ftld Andsupporting
confidence: 83%
See 3 more Smart Citations
“…Similarly, in the cortex of PPIA-/-mice, the 25-kDa TDP-43 fragment was significantly enriched in the detergent-insoluble fraction, while the full-length was not. Biochemical analysis of the detergent-insoluble fraction of the cortex of PPIA-/-mice indicated general increases in insoluble, ubiquitinated proteins and TIA1 stress granule marker, confirming PPIA's involvement in regulating protein homeostasis, as already suggested by other work in this laboratory (Filareti et al, 2017;Luotti et al, 2020). We recently reported that ALS patients have low PPIA levels and a concomitant shift toward increased protein partitioning in the insoluble fraction, with high levels of insoluble TDP-43 and hnRNPA2/B1 (Luotti et al, 2020).…”
Section: Ftld-tdp Is the Most Common Neuropathologic Type Of Ftld Andsupporting
confidence: 83%
“…We firstly reported that PPIA is altered in amyotrophic lateral sclerosis (ALS) animal models and patients (Basso et al, 2009;Massignan et al, 2007;Nardo et al, 2011). Next, we demonstrated that low levels of PPIA in peripheral blood mononuclear cells (PBMCs) of ALS patients are associated with an early onset of the disease (Filareti et al, 2017) and a short disease duration (Luotti et al, 2020). In agreement with this, PPIA deficiency exacerbated aggregation and accelerated disease progression in a SOD1 G93A mouse model of ALS (Lauranzano et al, 2015).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…In vivo , experimental induction of an HSPB5/8 homologue partially rescues TDP‐43 aggregation and increases life span in drosophila . In support of a protective role of HSPB in animal models of ALS, slow‐progressing SOD1 G93A mice have fivefold higher expression of HSPB5 when compared to fast‐progressing SOD1 G93A mice .…”
Section: Introductionmentioning
confidence: 90%